A Systematic Review on Cost-effectiveness Analyses of Therapeutic Drug Monitoring for Patients with Inflammatory Bowel Disease: From Immunosuppressive to Anti-TNF Therapy - Yao, Jiaqi; Jiang, Xinchan; You, Joyce H S (Inflammatory bowel diseases, 2021)
Abstract Background There is a growing body of primary evidence on the cost-effectiveness of applying therapeutic drug monitoring (TDM) for inflammatory bowel disease (IBD) management with various drug therapies and strategies. Objectives The aim of this study was to conduct a systematic review on model-based cost-effectiveness analyses of applying TDM for IBD management. Methods Literature search was conducted (up to October 2019) in Medline (Ovid), Embase (Ovid), Web of Science, Scopus, CINAHL Complete, and the Centre for Reviews and Dissemination. Studies published in the English language that met inclusion criteria were included: (1) patients with IBD, (2) TDM-based treatment was compared with a comparator, (3) types of analysis were cost-benefit, cost-consequence, cost-effectiveness, cost-utility, or cost analysis, and (4) analyses conducted by model-based evaluation. The study quality was assessed using Consolidated Health Economic Evaluation Reporting Standards. Results Six studies on drug monitoring for IBD patients (1 azathioprine and 5 infliximab) published in 2005 to 2019 were included. All studies targeted on patients with Crohn’s disease and reported TDM strategies to save cost when comparing with standard care. Four analyses evaluated both economic and clinical outcomes. Three analyses found the TDM strategies (for treatment initiation, advancement of therapy, or proactive monitoring) to improve clinical outcomes. One study found TDM strategies (reflex testing and concurrent testing) to gain lower quality-adjusted life years than standard care. Four of six (66.7%) studies achieved good to excellent rankings in quality assessment. Conclusions Compared with standard treatment without TDM, the TDM-guided strategies were consistently found to be cost-saving or cost-effective.